Searching for Political Fiscal Cycles in Hungary - Endrit Lami; Drini Imami (Contemporary Economics)
Hungary has had a remarkably high public debt throughout the transition, and it has continued to increase during recent years, exceeding 80% of the GDP. Its debt and fiscal deficit were the highest among the Visegrád countries during the transition. One factor triggering the debt increase may be elections-related fiscal policies. By analyzing quarterly data for Hungary, we found clear empirical evidence of fiscal expansion before elections and contractions afterwards. These events are widely known as political fiscal cycles. We observed statistically significant incremental increases in fiscal deficits as elections approach, both in nominal and in GDP ratios, followed by contractions after elections. Thus, it can be concluded that incumbents in Hungary are engaged in opportunistic political fiscal cycles by embracing expansionary fiscal policy before parliamentary elections. Our findings also suggest that political fiscal cycles in Hungary may be an underlying factor contributing to the accumulation of public debt.